Introduction to counseling : a condensed text - Fitch, Trey; Marshall, Jennifer L.; Matise, Miles (New York: Routledge, 2020)
"This CACREP aligned text outlines core concepts of the counseling profession alongside hundreds of practical study questions and case studies for students and professors. Written in a readable, concise format designed for adult learners, Introduction to Counseling is an essential resource that counseling students will want to keep long after graduation"--
Includes bibliographical references and index.
Keywords: Counseling -- Vocational guidance